Self-tuning generalized predictive control with input constraints - Królikowski, Andrzej; Jerzy, Damian (Zielona Góra: Uniwersytet Zielonogórski)
The handling of various input constraints in the self-tuning generalized predictive control (STGPC) problem of ARIMAX/ARMAX systems is considered. The methods based on the Lagrange multipliers and Lemke's algorithm are used to solve the constrained optimization problem. A self-tuning controller is implemented in an indirect way, and the considered constraints imposed on the control input signal are of the rate, amplitude and energy types.
Keywords: generalized predictive control; constraints; self-tuning; ARIMAX/ARMAX systems